The perception of allied health professionals on occupational therapy - Wan Yunus, Farahiyah; Ahmad Ridhuwan, Nuralia Fatiha; Romli, Muhammad Hibatullah (Hindawi, 2022)
Occupational therapy is a client-centered health profession and is a part of an interdisciplinary team. Effective interdisciplinary practice occurs when each professional understands the role of another professional in the team. This resulted in optimal referral among the professionals that can benefit the clients to receive good care and service. However, it seems that referrals to occupational therapy are becoming lesser by day in specific settings and hospitals in Malaysia. This brings a perspective if other professions in the healthcare team understand the role of occupational therapists. This study is aimed at exploring the perception and misconceptions of allied health professionals on the roles of occupational therapists. A focus group discussion was conducted among seven allied health professionals using a heuristic approach. The interview data were analyzed thematically. Themes developed were (i) awareness of occupational therapy ecosystem, (ii) in cooperating togetherness for the benefit of the client, and (iii) addressing the limitation to enhance the occupational therapy visibility. Findings found that the knowledge of other healthcare practitioners and clients on the occupational therapist’s role is still limited. Role confusion and overlapping are common among other allied health professionals. Occupational therapy needs to continually promote the profession’s role and identity for the maximum benefit to the client and overall improvement.